Estudo sobre o abandono escolar nos cursos do 1.º e 2.º ciclos de estudos do Instituto Politécnico de Bragança - Ferreira, Sérgio (2020)
The main objective of this research is to know the reasons for dropping out in the 1st and 2nd cycle programmes of the Polytechnic Institute of Bragança, in the period 2008-2012. The information was collected from 4107 students who dropped out of the IPB, between 2008-2012. The data collection of the 350 respondents was carried out by telephone from March to May 2014. The main results showed that a high dropout rate is around 20% per year. The reasons that led the student to leave the IPB are focus mainly on professional incompatibility, time incompatibility, being away from home-distance, insertion in the labour market, transfer to another educational institution, economic difficulties and personal problems, with family. Two profiles of students were identified, the Profile of students in the labour market and the Profile of students in the context of residence and school trajectory.